2018
DOI: 10.1016/j.ijcard.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific deletion of GSK-3β leads to cardiac dysfunction in a diet induced obesity model

Abstract: In summary, these results suggest that cardiac GSK-3β is crucial to protect against obesity-induced adverse ventricular remodeling and cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
3
20
3
Order By: Relevance
“…This causes an activation of the signal transduction molecule disheveled (Dvl) which, in turn, inhibits the (GSK-3β), the expression level of β-catenin increased. However, we found that the expression of p-GSK-3β was different from the results of previous studies (Gupte et al, 2018), which may be related to the time stage after myocardial infarction (Lal et al, 2014) or likely related different MI areas, such as MI and non-MI areas or maybe lcz696 likely regulating β-catenin and GSK-3β through two independent pathways, this will encourage us to explore further.…”
Section: Discussioncontrasting
confidence: 65%
“…This causes an activation of the signal transduction molecule disheveled (Dvl) which, in turn, inhibits the (GSK-3β), the expression level of β-catenin increased. However, we found that the expression of p-GSK-3β was different from the results of previous studies (Gupte et al, 2018), which may be related to the time stage after myocardial infarction (Lal et al, 2014) or likely related different MI areas, such as MI and non-MI areas or maybe lcz696 likely regulating β-catenin and GSK-3β through two independent pathways, this will encourage us to explore further.…”
Section: Discussioncontrasting
confidence: 65%
“…Heart weight did not differ between groups (p>0.05) ( Table 1). However, Gupte et al (28) found a higher absolute heart weight in rats that received a lipid-rich diet for 385 days, suggesting that, in the long term, the hyperlipidic diet can cause changes in the weight of this organ.…”
Section: Resultsmentioning
confidence: 99%
“…000664, The Jackson Laboratory) to generate Myh6-Cre +/– . A well-established TAM chow diet protocol was used to induce the CM-specific expression of Cre recombinase, as we previously reported 26, 27. Briefly, at 10 weeks of age, when physiological development is largely complete, all male mice were placed on a TAM chow diet (400 mg/kg, TD.130859, Harlan Sprague-Dawley, Indianapolis, Indiana) for 2 weeks followed by regular chow for an additional 4 weeks (to allow the clearance of TAM from the mice) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%